Fear of Crime and Feelings of Unsafety in European Countries: Macro and Micro Explanations in Cross‐National Perspective. Issue 2 (27th March 2013) - Visser, Mark; Scholte, Marijn; Scheepers, Peer
<x xml:space="preserve">Abstract</x> In this study, we set out to explain fear of crime and feelings of unsafety, using two waves of the European Social Survey (2006 and 2008) covering 25 European countries (N = 77, 674). The results of our multilevel analyses showed varying effects of contextual‐ and individual‐level characteristics on our two outcomes. Higher crime levels in countries increase the fear of crime; however, they do not affect feelings of unsafety. Social protection expenditure proves to be an important determinant of both fear of crime and feelings of unsafety. Moreover, distrust in the police, generalized social distrust, and perceived ethnic threat induce fear of crime as well as feelings of unsafety. Finally, policy implications are discussed.